PRZESTĘPSTWO DEZERCJI U SCHYŁKU OKRESU REPUBLIKAŃSKIEGO - Banyś, Tomasz J. (Zeszyty Prawnicze, 2016)
DESERTION AS A STANDALONE CRIME IN ANCIENT ROME Summary Desertion as a standalone crime in ancient Rome was penalised since the early republican period. While there are a limited number of sources available, certain characteristics of the act of desertion can be established, and so it can be stated to a certainty that absence from the signs or banners of a given military unit without proper authorisation, abandoning an officer, one’s post or the standard, or fleeing from combat were all considered desertion. The pressures of the later republican period demanded increased discipline in the army; therefore Gaius Julius Caesar began to treat the act of abandoning military equipment (weapons) as a form of desertion and introduced proper policy to counter such behavior, encouraging the troops to adorn their equipment so it would seem too precious to be left behind. This very form of desertion has long been considered to have emerged in later times, during the principate, however accounts given by Suetonius and Polyaenus on Caesar’s policy seem to imply the contrary, despite the general lack of development of military law during that time.